Evaluasi Sistem Jaringan Drainase Jalan Raya Menggunakan Sofware HEC-RAS - Andrea Oktaviani; Muhammad Oka Mahendra (Institut Teknologi Garut, 2025)
Baros Road, located in Serang Regency – Banten, is an important roadway that frequently experiences flooding during heavy rainfall. This study was conducted to evaluate the capacity of the existing drainage system, which is suspected to be unable to accommodate surface runoff, and to provide technical recommendations for its improvement. The methods employed included primary data collection through channel dimension surveys and secondary data in the form of annual maximum rainfall from the Merak Maritime Meteorological Station for the period 2015–2024. The design rainfall analysis was carried out using the Log Pearson Type III method, yielding a maximum rainfall of 378 mm for a 25-year return period. Rainfall intensity was then calculated for various durations and used in flood discharge calculations with the rational method. The highest discharge was recorded at approximately 2.95 m³/s, while the lowest was around 1.78 m³/s. A hydraulic simulation using HEC-RAS software showed that all STA (100–1000) under existing conditions were unable to contain the flood discharge, with water surface elevations exceeding channel elevations by up to 1.3 m. After improving channel dimensions and increasing bed slope, the re-simulation results indicated that all channels could accommodate the discharge, with a positive margin of up to 0.5 m between channel elevation and water surface. This study concludes that the Baros Road drainage system requires technical upgrades to anticipate peak discharges caused by extreme rainfall, thereby ensuring smoother transportation and minimizing damage to road infrastructure.